The interplay between customers' incidental and integral affects in value experience. (December 2022) - Sandberg, Birgitta; Hurmerinta, Leila; Leino, Henna M
Current understandings of emotional value focus on integral affects that are directly related to present judgements and choices. This neglects recent research on the complexity of affect and dismisses affects triggered by situations, events, or persons encountered in daily life outside of the decision-making situation or process; that is, incidental affects. In this article, we analyse the interplay between customers' incidental and integral affects in value experience during life transitions. Based on the qualitative data collected on real-estate services, we unveil the internal dynamics of affective value by showing the intrapersonal and interpersonal forms of interplay (spillover, ambivalence, divergence and convergence) between integral and incidental affects. This advances knowledge on the composition and dynamics of the concept of affective value and on the affective value experience in life transitions.